Total Synthesis of (6R, 10R, 13R, 14R, 16R, 17R, 19S, 20R, 21R, 24S, 25S, 28S, 30S, 32R, 33R, 34R, 36S, 37S, 39R)‐Azaspiracid‐3 Reveals Non‐Identity with the Natural Product. Issue 3 (13th December 2017) - Kenton, Nathaniel T.; Adu‐Ampratwum, Daniel; Okumu, Antony A.; Zhang, Zhigao; Chen, Yong; Nguyen, Son; Xu, Jianyan; Ding, Yue; McCarron, Pearse; Kilcoyne, Jane; Rise, Frode; Wilkins, Alistair L.; et al.
Abstract: A convergent and stereoselective total synthesis of the previously assigned structure of azaspiracid‐3 has been achieved by a late‐stage Nozaki–Hiyama–Kishi coupling to form the C21−C22 bond with the C20 configuration unambiguously established froml ‐(+)‐tartaric acid. Postcoupling steps involved oxidation to an ynone, modified Stryker reduction of the alkyne, global deprotection, and oxidation of the resulting C1 primary alcohol to the carboxylic acid. The synthetic product matched naturally occurring azaspiracid‐3 by mass spectrometry, but differed both chromatographically and spectroscopically. Abstract : A convergent and stereospecific total synthesis of the previously assigned structure of the marine neurotoxin azaspiracid‐3 reveals non‐identity with the natural product. Therefore structural revision of the primary azaspiracids is necessary.